2015
DOI: 10.1517/14712598.2015.1066331
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cellular and molecular immunomodulatory pathways by vitamin A and flavonoids

Abstract: Introduction A detailed study of reports on the immunomodulatory properties of vitamin A and select flavonoids may pave the way for using these natural compounds or compounds with similar structures in novel drug and vaccine designs against infectious and autoimmune diseases and cancers. Areas Covered Intracellular transduction pathways, cellular differentiation and functional immunomodulatory responses have been reviewed. The reported studies encompass in vitro, in vivo preclinical and clinical studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 147 publications
(203 reference statements)
0
20
0
1
Order By: Relevance
“…This is the first study in which the combination of vitamins A and E and a catechin synergistically enhanced not only B‐cell responses, but also Th1, Th2 and CD8 + T‐cell responses, in the absence of select innate, pro‐inflammatory responses. Studies on the immunomodulatory properties of vitamins and flavonoids are gaining momentum . Although in a previous publication we had used retinoic acid and catechin hydrate to generate NIDS, in the current study, we successfully replaced catechin hydrate with EGCG, and retinoic acid with RP, because of their low cost for large‐scale manufacturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study in which the combination of vitamins A and E and a catechin synergistically enhanced not only B‐cell responses, but also Th1, Th2 and CD8 + T‐cell responses, in the absence of select innate, pro‐inflammatory responses. Studies on the immunomodulatory properties of vitamins and flavonoids are gaining momentum . Although in a previous publication we had used retinoic acid and catechin hydrate to generate NIDS, in the current study, we successfully replaced catechin hydrate with EGCG, and retinoic acid with RP, because of their low cost for large‐scale manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory roles of the various vitamins and flavonoids remain controversial as although some studies suggest that some vitamins and flavonoids enhance immunity, other studies, using the same compounds, show that they in fact suppress immunity . Specifically, immunomodulation by vitamins A and D includes both up‐ and down‐regulation of certain immune responses, varying by the type of immune response, pathogen and host …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that phytochemicals such as antioxidants absorbed from tea, fruit, and medicinal plants could not only reduce free radical formation and scavenge free radicals but also possess considerable antifatigue activity [14]. Flavonoids from plants are considered to be one of the most effective groups of phytochemicals due to their wide range of pharmacological activities, such as antioxidative, anti-inflammatory, immunomodulatory, antidiabetic, and antitumor effects [1518]. Flavonoids have also been widely studied as a new group of natural antifatigue substances; many studies have revealed that flavonoid supplementation enhanced the endurance exercise performance of fatigued rats by reducing their muscle fatigue [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…The immunomodulatory properties of each of the components of NIDS have been discussed extensively in two recent reviews [10,11]. Moreover, the adjuvant effect of the NIDS has been demonstrated in two recent publications, in which NIDS was shown to enhance adaptive CD4+ TH, CD8+ IFNγ+, and B cell antibody responses [8,9].…”
Section: Discussionmentioning
confidence: 99%